A new flood vulnerability index adapted for the pre-Saharan region. Issue 1 (2nd January 2021) - Karmaoui, Ahmed; Balica, Stefania
ABSTRACT: Moroccan Pre-Saharan zone is an oasis system, which it is characterized by extreme events, like drought and flood. The flood risks will likely increase in frequency and magnitude due to global and regional climate change. Flood tends to have an important impact on isolated and poor regions such as oasis regions. This extreme event impacts are seen at the same time in social and economic sectors and accelerated by the dry land physical and environmental drivers like land use, topography, proximity to rivers. In Morocco, the use of composite indices to evaluate natural disasters is new. The reduction of flood vulnerability cannot be accomplished by one sector alone. Therefore, it is a need to use a multidisciplinary approach to measure vulnerability. This paper aims to develop and analyze the applicability of a new index in the pre-Saharan region of Morocco, the Oasean flood Vulnerability Index. It was determined for six components: climatic, physiographic, land use, anthropogenic, economic and access to services. These components can help to find out the priority mechanisms and sectors of flood vulnerability in order to take urgent measures. For this study five sub-catchments were selected: The proposed methodology to calculate an OFVI provides an approach to quantify how much floods are affecting or can affect a sub-catchment or an urban area in pre-Saharan regions.